Customer satisfaction towards service quality of counter service at Syarikat Air Melaka Berhad (SAMB) Jalan Hang Tuah / Hazirah Masrom and Nor Nadziha Asmari - Masrom, Hazirah; Asmari, Nor Nadziha (Faculty of Business and Management, 2015)
This research is conducted to examining the customer satisfaction level through service quality of Syarikat Air Melaka Berhad (SAMB). A survey on customer satisfaction level through service quality was conducted among customer in SAMB involved 100 respondents. The attributes of service quality such as tangible, reliability, responsiveness, assurance and empathy have been identified in order to investigate whether or not these factor have significant relationship with customer satisfaction. From this study, the researcher can able to determine the current level of customers satisfaction that they perceive at counter service provided by Syarikat Air Melaka Berhad (SAMB), to identify the significant relationship between SERVQUAL elements and customers satisfaction towards service quality at counter service provided by Syarikat Air Melaka Berhad (SAMB) and to identify which SERVQUAL elements that has the most relationship on customer satisfaction towards service quality at counter service provided by Syarikat Air Melaka Berhad (SAMB).